(untitled) (gjstudies, 2019)
This research investigates the evolving and multifaceted roles of audit committees instrengthening financial oversight, moving beyond traditional compliance-focused models to propose a novel, integrated framework. While existing literature predominantlyexamines audit committees through a regulatory or agency theory lens, this study introduces a hybrid methodology combining computational text analysis of corporate disclosures with a behavioral governance simulation. We analyze a unique, hand-collecteddataset of 450 audit committee charters and minutes from 1998 to 2004, applying natural language processing techniques to map the semantic shift in stated responsibilitiesand perceived efficacy. Concurrently, we develop an agent-based simulation modelthat incorporates behavioral factors—such as committee member cognitive diversity,risk propensity, and social dynamics—to explore how these non-structural elements influence oversight outcomes. Our findings reveal a significant, previously under-exploreddivergence between the formal, procedural duties documented in charters and the informal, deliberative practices captured in minutes, which are more predictive of financial reporting quality. The simulation results demonstrate that committees exhibitinghigher cognitive diversity and moderate levels of constructive conflict achieve superior oversight, reducing the incidence of material misstatements by an estimated 22%compared to homogenous, consensus-driven groups, even when controlling for standardindependence and financial expertise metrics. This research contributes originality bybridging computational social science with corporate governance, challenging the primacy of structural attributes, and offering a dynamic, process-oriented view of auditcommittee effectiveness. The proposed framework provides a novel tool for boards,regulators, and investors to assess the qualitative dimensions of oversight strength.